Racism Paradox in the Play of Lorraine Hansberry’s “A Raisin in the Sun” - Rita Napitupulu; Theressa Fang (Budapest International Research and Critics University, 2022)
For this research, the writer analyzes about the racism paradox through the play of “A Raisin in The Sun,” written by the black famous author, Lorraine Hansberry. The story tells about the lives of an African-American family, the Youngers, who like many other African-American families migrated from the South to the North to leave behind the social, economic and educational oppression. They attempt to improve their financial circumstances with an insurance payout following the death of the father, and deals with matters of housing discrimination, and racism. The writer applies the qualitative research, and library research in doing the analysis of the play. In the analysis, the writer finds the function of paradox that it can reveal the injustice, faced by the black people. They are inferior as treated by the whites in which it is actually so contradicted with the declaration of Independence Day they have. Then why paradox is used in the play, the writer thinks that it becomes a tool for the writer to express what the black people face which is very different from the life of the white people in real.